Pengaruh Agroinput Terhadap Kinerja Agribisnis Mangga Di Kecamatan Sedong Kabupaten Cirebon - Fitri Awaliyah; Rahman Syakur; Tintin Febrianti; Bobby R Saefudin; Dina Dwirayani (Paradigma Agribisnis, 2024)
Agribusiness subsystem is very important in agribusiness performance, one of which is agroinput. Agroinput is one of the success factors for mango agribusiness performance. This study aims to determine whether there is an influence between agro-input on the performance of mango agribusiness in Sedong District, Cirebon Regency. The method used in this research is descriptive quantitative. The number of samples in this study were 50 samples. The data analysis technique used in this study is to use a simple linear regression with the help of SPSS 23.0 for windows. The results showed that agro-input had an influence of 41.1% on agribusiness performance. The influence of agro-input is in the factors that provide agricultural production facilities such as the provision of land, inputs, wages and capital which increase income or contribute to agribusiness performance as a support for mango agricultural production facilities from the start of production.Keywords: Agroinput, Agribusiness Performance and Mango Farmers.